Nonlinear Whole Ecology, Change of Entropy, Hypercycle, Talent Ecology and Chinese Cultural-Social Ecology - Chang, Yi-Fang (European Journal of Applied Sciences, 2022)
Ecology is closely related to the rise and fall of human society. First, we propose the nonlinear whole ecology and its four basic rules. Second, entropy plays an important role in ecological economics, and the cycle of resources and the general recycling economy cannot be a single increase process of entropy, we research possible entropy decrease. Third, in order to achieve sustainable development, society must realize the recycling economy. We study the applications of hypercycle in ecology, and corresponding equations of ecosystem. The key factor in the cycle is the conversion of waste. Fourth, we propose the talent ecology, which studies the relations among talent and circumstances (esp., the social circumstances), and search its three basic principles. The base of talent is education. The mechanism of the academic development is freedom. The aim is innovation. The talent ecology must encourage the academic diversity. Fifth, the structure-function-result mode of ecosystem is proposed. Sixth, we discuss the recycling ecosystem of traditional Chinese agriculture, and Chinese cultural-social ecology.